Pemberdayaan Rumah Tahfidz Smart Qur’an Depok Dalam Pembelajaran Kesantunan Berbahasa - Tri Pujiati (Lembaga Penelitian, Publikasi Ilmiah dan Pengabdian kepada Masyarakat (LP3M), 2023)
Polite language is one of the important things that must be considered in social life, especially us as a society that is famous for its eastern ethics and culture. Politeness needs to be instilled in mosque children from an early age so that a polite culture is instilled in them. The existence of empowerment activities for children at the Tahfidz Smart Qur'an Depok House in learning politeness in this language is needed as an effort to solve problems related to shifting politeness in children who are in the Baitul Ma'mur mosque, Depok. This issue was raised due to the many complaints from parents who felt that their children had language that was not polite enough when talking to older people or to younger people. The empowerment of children at the Tahfidz Smart Qur'an Depok House is packaged in a unique and attractive form so that children are interested in participating in this activity. This empowerment is packaged during the month of Ramadan through Islamic boarding school activities to fill the time of breaking the fast. The empowerment method used is an Asset-Based Community-driven Development (ABCD) approach that focuses on exploiting the potential that exists in the community in the surrounding environment. This program is carried out as an effort to improve the polite language skills of Muslim children in children at the Tahfidz Smart Qur'an Depok House. The results of empowering children in the mosque environment show that this program has succeeded in increasing children's ability to use polite language according to the Muslim version. This program can be used as an alternative for learning polite Muslim children's version in the mosque environment so that it can be applied in everyday life by children and can be adopted by other Qur'an Education Institutions (LPQ).